Immobilization of uranium by S-NZVI and UiO-66-NO2 composite through combined adsorption and reduction. (1st March 2023) - Zhang, Di; Tang, Hao; Zhao, Bing; Liu, Lijie; Pang, Hongwei; Wang, Xiangxue; Yu, Shujun
Abstract: Radioactive uranium removal plays a key role in energy development and environmental security. Sulfide nanoscale zero-valent iron (S-NZVI) has good antioxidant capacity, dispersibility and activity to eliminate U(VI) from wastewater, but the removal efficiency is limited. To improve the reduction and adsorption capacity of S-NZVI, through treating Fe 3+ solution by nitro-functionalized UiO-66 (UiO-66-NO2 ) with high porosity, UiO-66-NO2 enhanced S-NZVI adsorbent (S-NZVI/UiO-66) was prepared by liquid phase reduction method. The smaller size and larger specific surface area of S-NZVI/UiO-66 were confirmed by a variety of characterization techniques. Based on the excellent surface structure and reactivity, the U(VI) removal capacity of S-NZVI/UiO-66 (895 mg g −1 ) was much better than S-NZVI (434 mg g −1 ) and UiO-66-NO2 (267 mg g −1 ). The impacts of pH, background ion strength, coexisting ions and different water environments on adsorption were studied via macroscopic batch experiments. The results showed that S-NZVI/UiO-66 could remove U(VI) adequately in a wide pH range. The removal rate was basically not affected by the concentration of NaNO3, demonstrating that the adsorption process of U(VI) on S-NZVI/UiO-66 tended to inner surface complexation. From XPS technique combined with the results of batch adsorption experiments, it was clear that the elimination mechanisms of U(VI) by S-NZVI/UiO-66 were mainly the physical adsorption, electrostatic attraction and complexation of UiO-66-NO2, and the reduction and complexation of S-NZVI. Therefore, it is believed that S-NZVI/UiO-66 has a great potential to be an excellent adsorbent in the field of the environment remediation. Moreover, S-NZVI/UiO-66 promises to be a novel nanomaterial for solving the problem of radionuclide contamination in practical environments. Graphical abstract: Image 1 Highlights: The pretreatment of UiO-66-NO2 can effectively reduce the size of S-NZVI. S-NZVI/UiO had a better specific surface area than the original S-NZVI. The practical application potential of S-NZVI/UiO was confirmed. The removal mechanisms were adsorption and reduction.